Methods to Analyze Proteins from Soils: Method to analyze protien from Soilsh - Mukhtar, Salma; Laaldin, Nayaab; Mehnaz, Samina; Abdulla Malik, Kausar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Recent advances in molecular techniques, especially system approaches at DNA, RNA and protein levels have opened an emerging field in microbial ecology. These approaches can be used to identify the specific microbial genes and their functions directly from environmental samples. Among the different ‘omics’ approaches, metaproteomics is used to study microbial ecology and it plays an important role in the determination of microbial functionality. It provides detail about the structure and function of microbial populations from soil samples. However, proteins isolation and purification is very challenging due to complexity of soil samples. Only a few methods give high quality of extracting proteins and other methods can only be used to separate proteins using SDS electrophoresis but they are unable to characterize and identify specific proteins present in a soil sample. This review has mainly focused on recent advances in metaproteomic strategies to understand the structure and function of soil microbial communities. Three methods for protein extraction from soil samples were explained here, e.g., (1) using the phenol extraction method, (2) cell lysis method using different concentrations of SDS and alkaline lysis method using NaOH. For purification and identification of proteins, HPLC, FPLC, 2D-LC, LC-MS, MALDI-TOF and shotgun proteomics analyses were explained.